Pengaruh Kualitas Layanan Kepercayaan dan Promosi Terhadap Kepuasan Nasabah dalam menggunakan Jasa Pinjaman ULaMM (Unit Layanan Modal Mikro) PT PNM (Permodalan Nasional Madani) Unit Kota Agung, Tanggamus - Hariono, Tri; Listyaningsih, Erna; Indriani, Wiewiek (Jurnal Jejama Manajemen Malahayati, 2021)
This research was purposed on testing and proving the influences of (1) the effect of service quality (physical evidence, reliability, responsiveness, assurance, empathy) on customer satisfaction ULaMM (Micro Capital Service Unit) PT PNM (Permodalan Nasional Madani) Kota Agung Unit, Tanggamus. (2) The influence of trust on PT PNM (Permodalan Nasional Madani) Unit Kota Agung Unit, Tanggamus, ULaMM (Micro Capital Service Unit) customer satisfaction. (3) Effect of Promotion on PT PNM (Permodalan Nasional Madani) Unit Kota Agung Unit, Tanggamus, ULaMM (Micro Capital Service Unit) customer satisfaction. The population in this study is the customers of the ULaMM Kota Agung Unit, Tanggamus for the period 2016-2018, amounting to 1,665 people. The sampling method uses purposive sampling with 324 respondents. The sampling criteria are a) customers who use ULaMM services for at least 1 year; b) Aged 21 years, because at that age a person is eligible to enter into an agreement in accordance with the terms of the agreement. The variables used are as many as 5 variables. The analytical tool used is multiple regression analysis. The analysis shows that: a) physical evidence variable influences customer satisfaction. b) variable reliability affects customer satisfaction. c) variable responsiveness affects customer satisfaction. d) guarantee variables affect customer satisfaction. e) the empathy variable has no effect on customer satisfaction. f) the variable of trust does not affect customer satisfaction. g) promotion variable does not affect customer satisfaction.Keywords: Quality of Physical Evidence Services, Reliability, Responsiveness, Empathy, Guarantee, Customer Trust and Promotion